2020
DOI: 10.1364/boe.395843
|View full text |Cite
|
Sign up to set email alerts
|

Visible light optical coherence tomography angiography (vis-OCTA) facilitates local microvascular oximetry in the human retina

Abstract: We report herein the first visible light optical coherence tomography angiography (vis-OCTA) for human retinal imaging. Compared to the existing vis-OCT systems, we devised a spectrometer with a narrower bandwidth to increase the spectral power density for OCTA imaging, while retaining the major spectral contrast in the blood. We achieved a 100 kHz A-line rate, the fastest acquisition speed reported so far for human retinal vis-OCT. We rigorously optimized the imaging protocol such that a single acquisition to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 37 publications
1
41
0
Order By: Relevance
“…Pi et al 80 utilized vis-OCT angiography to assess oxygen saturation in the retinal capillary beds of rats in response to changes in the inspired concentration of oxygen. Song et al 81 performed microvascular oximetry of the capillary network in the foveal region of human volunteer subjects, finding that oxygen saturation was between the retinal arterioles and venules as expected. As vis-OCT expands into other fields such as OCT angiography, 82 several practical challenges are still being addressed before systems are implemented into clinical practice.…”
Section: Newer Approachesmentioning
confidence: 63%
“…Pi et al 80 utilized vis-OCT angiography to assess oxygen saturation in the retinal capillary beds of rats in response to changes in the inspired concentration of oxygen. Song et al 81 performed microvascular oximetry of the capillary network in the foveal region of human volunteer subjects, finding that oxygen saturation was between the retinal arterioles and venules as expected. As vis-OCT expands into other fields such as OCT angiography, 82 several practical challenges are still being addressed before systems are implemented into clinical practice.…”
Section: Newer Approachesmentioning
confidence: 63%
“…We selected one vein (V1) and one artery (V2) with diameters of 168 µm and 120 µm, respectively. The four normalization methods are Method 1: no normalization, as reported by Yi et al (17), Chen et al (25), and Pi et al (22); Method 2: normalization by the RNFL, which is typically anterior to the retinal vessels, as reported by Song et al (26) and suggested by Chong et al (19, 20); Method 3: normalization by the anterior vessel wall (AW), which can be highly reflective and is immediately above the blood signal; and Method 4: normalization by the start of signal decay in the blood (z d ). We applied SDBG correction (28) for all four methods.…”
Section: Resultsmentioning
confidence: 99%
“…Both the sample-dependent and system-dependent SCs have magnified and more unpredictable influences on sO 2 measurement accuracy in human imaging than in small animal imaging because of the reduced light illumination power due to ocular laser safety and patient comfort, stronger eye motion, and larger variation in retinal anatomy (18, 19, 26, 32). In addition, it is more challenging to identify PWs of all human retinal vessels due to enlarged vessel diameters.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Song et al reported vis-OCT retinal imaging at an A-line rate of 100 kHz [19]; however, they limited the illumination bandwidth to 35 nm to increase power density, which degraded axial resolution to ~ 5 µm and did not solve the RIN problem.…”
Section: Introductionmentioning
confidence: 99%